2019
DOI: 10.1056/nejmoa1811403
|View full text |Cite
|
Sign up to set email alerts
|

Marine n−3 Fatty Acids and Prevention of Cardiovascular Disease and Cancer

Abstract: Background Whether omega-3 fatty acid supplementation reduces risk of cardiovascular disease or cancer remains unclear. Methods The VITamin D and OmegA-3Trial (VITAL) was a randomized, placebo-controlled, 2X2 factorial trial of vitamin D3 (2000IU/day) and marine omega-3 fatty acids (1 g/day) in the primary prevention of cardiovascular disease and cancer among 25,871 U.S. men aged ≥50 and women aged >55, including 5,106 African Americans. Primary endpoints were major cardiovascular events (myocardial infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
665
1
20

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 776 publications
(704 citation statements)
references
References 40 publications
18
665
1
20
Order By: Relevance
“…This notion has emerged in trials of homocysteine (HCy)‐lowering B vitamins to slow cognitive decline and reduce total brain atrophy in people with hyperhomocysteinemia and higher baseline n‐3 polyunsaturated fatty acid (PUFA) in circulation [7,9]. These findings are consistent with several other nutritional interventions in older adults that targeted those with suboptimum nutritional status in primary [6] or secondary analyses [10] or determined a posteriori that baseline nutritional status dictated efficacy [2,3,8].…”
Section: Introductionmentioning
confidence: 55%
“…This notion has emerged in trials of homocysteine (HCy)‐lowering B vitamins to slow cognitive decline and reduce total brain atrophy in people with hyperhomocysteinemia and higher baseline n‐3 polyunsaturated fatty acid (PUFA) in circulation [7,9]. These findings are consistent with several other nutritional interventions in older adults that targeted those with suboptimum nutritional status in primary [6] or secondary analyses [10] or determined a posteriori that baseline nutritional status dictated efficacy [2,3,8].…”
Section: Introductionmentioning
confidence: 55%
“…Beyond the CVD risk, statins have been attributed to a favorable effect on hepatocellular carcinoma incidence in a case‐control study, and thus their use can be beneficial from both a liver and CVD perspective. Additional measures to improve the CV risk could be the addition of omega n‐3 fatty acid supplements that were recently shown to decrease CV risk …”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the results of two major trials (ASCEND and VITAL) of omega‐3 PUFA (1 g per day) for primary prevention of CV disease were reported . Neither trial reported a significant reduction in the risk of a composite cardiovascular endpoint in the omega‐3 PUFA group compared to the placebo group, although the VITAL trial reported a significantly lower rate of myocardial infarction in the omega‐3 PUFA arm.…”
Section: Randomized Controlled Trials and Meta‐analysesmentioning
confidence: 99%